Clays and Clay Minerals, Vol. 56, No. 3, 344–358, 2008. - Cruz, Maria Dolores Ruiz (The Clay Minerals Society, 2008)
The structural significance of micas with Na-K intermediate composition, and their chemical and structural evolution at increasing metamorphic grade have been investigated in Triassic rocks from the transition between the Mala´guide and Alpuja´rride complexes (Internal zones of the Betic Cordillera, Spain). Micas were studied by X-ray diffraction (XRD) and by scanning and transmission electron microscopy (SEM/TEM). Three samples, belonging to the late diagenesis and to the low and medium anchizone, were selected for this study. Na-bearing mica appears as submicroscopic packets intergrown in parallel with K-mica, becoming more compositionally uniform with increasing grade. The diagenetic sample contains illite, minor paragonite, and two main populations of intermediate Na-K micas, with average compositions Ms60Prg40 and Ms35Prg65, respectively, where Ms represents muscovite and Prg, paragonite. The lattice-fringe images of mica packets with intermediate compositions suggest the presence of random mixed-layered paragonite-muscovite. Under low anchizonal conditions the amount of discrete paragonite increases and the Na-K intermediate mica has a mean composition of Ms40Prg60. The TEM images suggest that the packets with intermediate composition are solid solutions of paragonite and illite. Micas with Na-K intermediate composition are lacking in the sample with the highest metamorphic grade. In this sample, paragonite and muscovite coexist with mica, with composition intermediate between paragonite and margarite. The lattice-fringe images of these Na-Ca-bearing packets suggest that they consist of irregularly shaped domains enriched either in Na or in Ca. Our data indicate that Na+K-bearing micas have several origins: detrital stacks of K- and Na-bearing micas coexist with authigenic phases, formed from dickite in the diagenetic, coarse-grained samples, and perhaps from smectite-bearing mixed-layers or detrital illite, in the fine-grained rocks. The changes observed at increasing metamorphic grade can be related to the influence of the lithology, the metamorphic grade, and the different geological settings. Intermediate Na-Ca mica appears to have grown from paragonite, with calcite as the source of Ca.
Na-bearing White Micas From Triassic Rocks Of The Transition Between The Malaguide And Alpujarride Complexes (betic Cordillera, Spain).
Clays and Clay Minerals, Vol. 56, No. 3, 344–358, 2008. Na-bearing White Micas From Triassic Rocks Of The Transition Between The Malaguide And Alpujarride Complexes (betic Cordillera, Spain). Maria Dolores Ruiz Cruz. DOI: 10.1346/CCMN.2008.0560305. Copyright © 2008, The Clay Minerals Society.
Keywords: Periodicals; Geology; Intermediate Na-Ca mica; Intermediate Na-K mica; Low-grade Metamorphism; Muscovite; Paragonite